2014
DOI: 10.1063/1.4873118
|View full text |Cite
|
Sign up to set email alerts
|

Understanding molecular interactions in light-emitting polymer bilayers: The role of solvents and molecular structure on the interface quality

Abstract: We explore the donor/acceptor interaction between distinct polymers at sequential bilayer interfaces to understand if their emission is influenced by the solvent. Resonant soft X-ray reflectivity and near-edge X-ray absorption fine structure measurements were used to investigate optical and morphological properties of polymer stacks, which were made using polymer chain structures diluted with different or equal solvents. We identified coupled and uncoupled bilayer systems using as a probe the exciton energy tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The techniques based on resonant X-ray elastic scattering using both hard X-rays (Bai et al, 1995;Vaknin et al, 2003;Lé toublon et al, 2004;Kim et al, 2004;Strzalka et al, 2004;Park et al, 2006;Park & Fenter, 2007;Kemik et al, 2011) and soft X-rays (Fink et al, 2013) provide an opportunity for studying different properties and the associated parameters in condensed matter physics. Resonant soft X-ray elastic scattering has been used to study polymeric and organic materials (Wang et al, 2005;Araki et al, 2006;Mitchell et al, 2006;Mezger et al, 2011;Collins et al, 2012;Pasquali et al, 2014;Stone & Kortright, 2014;Pauli et al, 2014), to study ionic liquids (Mezger et al, 2013), for the electronic and structural analysis of hard matter (Nayak et al, 2006;Valvidares et al, 2010;Ksenzov et al, 2010;Park et al, 2013;Krumrey et al, 2011;Filatova et al, 2012;Nayak et al, 2010Nayak et al, , 2015Nayak & Lodha, 2013a,b;Macke et al, 2014) and to obtain the magnetization profile in magnetic structures (Tonnerre et al, 1995;Sacchi et al, 1998;Benckiser et al, 2011;Bertinshaw et al, 2014;Macke & Goering, 2014). However, very little effort has previously been put into using resonant soft X-ray scattering to measure the spatially resolved chemically sensitive low-Z atomic profile of low-contrast interface structures.…”
Section: Introductionmentioning
confidence: 99%
“…The techniques based on resonant X-ray elastic scattering using both hard X-rays (Bai et al, 1995;Vaknin et al, 2003;Lé toublon et al, 2004;Kim et al, 2004;Strzalka et al, 2004;Park et al, 2006;Park & Fenter, 2007;Kemik et al, 2011) and soft X-rays (Fink et al, 2013) provide an opportunity for studying different properties and the associated parameters in condensed matter physics. Resonant soft X-ray elastic scattering has been used to study polymeric and organic materials (Wang et al, 2005;Araki et al, 2006;Mitchell et al, 2006;Mezger et al, 2011;Collins et al, 2012;Pasquali et al, 2014;Stone & Kortright, 2014;Pauli et al, 2014), to study ionic liquids (Mezger et al, 2013), for the electronic and structural analysis of hard matter (Nayak et al, 2006;Valvidares et al, 2010;Ksenzov et al, 2010;Park et al, 2013;Krumrey et al, 2011;Filatova et al, 2012;Nayak et al, 2010Nayak et al, , 2015Nayak & Lodha, 2013a,b;Macke et al, 2014) and to obtain the magnetization profile in magnetic structures (Tonnerre et al, 1995;Sacchi et al, 1998;Benckiser et al, 2011;Bertinshaw et al, 2014;Macke & Goering, 2014). However, very little effort has previously been put into using resonant soft X-ray scattering to measure the spatially resolved chemically sensitive low-Z atomic profile of low-contrast interface structures.…”
Section: Introductionmentioning
confidence: 99%
“…Since the electron densities of the donor and acceptor films vary by more than 10%, XRR can resolve the compositional variation across the buried donor/acceptor interfaces in the bilayer films. 46,47 The reflectivity traces of the bilayer films and their modeled electron density profiles are shown in Figure 4a and 4b−d, respectively. The reflectivity traces of the as-evaporated and annealed bilayer films are identical, indicating that the bilayer structure is retained on annealing in each case.…”
Section: Resultsmentioning
confidence: 99%
“…Several research groups addressed this issue by substituting the alkyl chain of PFO, which gave rise to a low-energy emission when replaced with oxygen, , or by synthesizing polymers with new units. , They synthesized the polymers with pure blue emission, however, the synthesis process consisted of a series of complex steps. On the other hand, other researchers reported that the optical and electrical properties of the emission layer could be manipulated by interlayer diffusion, which consists in a partial intermixing of two layers in contact and induces interactions between the two materials. Amongst these studies, Zhu et al and He et al successfully reported the control of PFO properties by interlayer-mixing phenomenon with the bottom layer through in situ spin-coating process. This process involves a simple method compared to the synthesis of new PFO-based polymer and can help controlling the phase of PFO.…”
Section: Introductionmentioning
confidence: 99%